Plasma HIV viral rebound following protocol-indicated cessation of ART commenced in primary and chronic HIV infection. - Elizabeth Hamlyn; Fiona M Ewings; Kholoud Porter; David A Cooper; Giuseppe Tambussi; Mauro Schechter; Court Pedersen; Jason F Okulicz; Myra McClure; Abdel Babiker; Jonathan Weber; Sarah Fidler; et al. (PLoS ONE)
Objectives The magnitude of HIV viral rebound following ART cessation has consequences for clinical outcome and onward transmission. We compared plasma viral load (pVL) rebound after stopping ART initiated in primary (PHI) and chronic HIV infection (CHI). Design Two populations with protocol-indicated ART cessation from SPARTAC (PHI, n = 182) and SMART (CHI, n = 1450) trials. Methods Time for pVL to reach pre-ART levels after stopping ART was assessed in PHI using survival analysis. Differences in pVL between PHI and CHI populations 4 weeks after stopping ART were examined using linear and logistic regression. Differences in pVL slopes up to 48 weeks were examined using linear mixed models and viral burden was estimated through a time-averaged area-under-pVL curve. CHI participants were categorised by nadir CD4 at ART stop. Results Of 171 PHI participants, 71 (41.5%) rebounded to pre-ART pVL levels, at a median of 50 (95% CI 48-51) weeks after stopping ART. Four weeks after stopping treatment, although the proportion with pVL ≥ 400 copies/ml was similar (78% PHI versus 79% CHI), levels were 0.45 (95% CI 0.26-0.64) log(10) copies/ml lower for PHI versus CHI, and remained lower up to 48 weeks. Lower CD4 nadir in CHI was associated with higher pVL after ART stop. Rebound for CHI participants with CD4 nadir >500 cells/mm(3) was comparable to that experienced by PHI participants. Conclusions Stopping ART initiated in PHI and CHI was associated with viral rebound to levels conferring increased transmission risk, although the level of rebound was significantly lower and sustained in PHI compared to CHI.